Analisis dan Perancangan Sistem Informasi Manajemen Inventori Berbasis Website Menggunakan Standar ISO/IEC 25010 (Studi Kasus: PT Teknologi Informatika Solusindo) - Raihanullah Raihanullah; Daffa Alif Ruriyanto; Chairul Anwar (Journal of Information Systems and Business Technology, 2026)
Inventory management at PT Teknologi Informatika Solusindo continues to face practical challenges, largely due to processes that are not yet fully integrated into a digital system. The continued reliance on manual and semi-computerized recording leads to inconsistencies in data, difficulties in asset tracking, and a higher likelihood of errors or data loss. These conditions directly affect operational performance and reduce the effectiveness of decision-making. In response to these issues, this study focuses on designing a web-based inventory information system, preceded by an in-depth identification of user requirements. System development is carried out iteratively using the Prototype approach to ensure adaptability to real user needs. The design also refers to the ISO/IEC 25010 standard to ensure software quality in terms of functionality, reliability, and usability. The resulting system is expected to improve data quality, enhance inventory management effectiveness, and provide more accurate and accessible information to support better decision-making.